The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.11648/j.ab.20190702.12
|View full text |Cite
|
Sign up to set email alerts
|

Catechin Attenuates the Effect of Combined Arsenic and Deltamethrin Toxicity by Abrogation of Oxidative Stress and Inflammation in Wistar Rats

Abstract: This study was aimed at evaluating the protective role of catechin (CT) against toxicity induced by combined exposure to arsenic (As) and deltamethrin (DM) in rats. Thirty-five (35) male Wistar rats were divided into 5 groups of 7 animals each. Treatment of each group was as follows: Control (C) administered corn oil (1ml kg -1 ), catechin only (CT) at 40mg kg -1 , As+DM administered As (100ppm) in their drinking water and DM at a dose of 7.5mg kg -1 (1/20 th LD 50 ), As+DM-CT 40 treated as As+DM in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Another chemical factor that people face in the workplace is exposure to metals and pesticides. In this study, by reviewing the studies that examined the consequences of metals and pesticides simultaneously, we indicated that having two risk factors have a greater effect on the body than either one alone ( 7 , 46 ). Metals and pesticides have additive and even opposite effects.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another chemical factor that people face in the workplace is exposure to metals and pesticides. In this study, by reviewing the studies that examined the consequences of metals and pesticides simultaneously, we indicated that having two risk factors have a greater effect on the body than either one alone ( 7 , 46 ). Metals and pesticides have additive and even opposite effects.…”
Section: Discussionmentioning
confidence: 98%
“…According to the studies that investigated the effect of physical and chemical factors on oxidative stress parameters, we showed that long-term occupational exposure to a number of environmental toxins, such as lead and cadmium, might cause oxidative stress and then act as a mechanism for negative effects on body systems ( 45 ). Regarding the physical aspects of the work environment, each of them, including electromagnetic waves and radiation, have the capacity to cause oxidative stress ( 44 , 46 , 47 ). In general, oxidative stress is caused by simultaneous exposure to physical and chemical stimuli.…”
Section: Discussionmentioning
confidence: 99%